Are any medications effective for retrograde ejaculation?. Issue 10 (October 2015) - Pejic, Rade N.; Smith, Kiernan A.
Abstract : Evidence‐Based Answer : There are no placebo‐controlled trials to guide the treatment of retrograde ejaculation. Sympathomimetic and anticholinergic medications have been recommended as possible treatments (SOR: C, based on case series and international guideline).